2021
DOI: 10.1371/journal.pone.0260514
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic transcriptome analysis identifies genes, polymorphisms and pathways involved in the fatty acids metabolism in sheep

Abstract: Fatty acids (FA) in ruminants, especially unsaturated FA (USFA) have important impact in meat quality, nutritional value, and flavour quality of meat, and on consumer’s health. Identification of the genetic factors controlling the FA composition and metabolism is pivotal to select sheep that produce higher USFA and lower saturated (SFA) for the benefit of sheep industry and consumers. Therefore, this study was aimed to investigate the transcriptome profiling in the liver tissues collected from sheep with diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Further insights into the interaction between the candidate lncRNA MSTRG.259847.2 and its target gene SMAD2 were substantiated in sheep pituitary cells [44]. By utilizing RNA-seq, an investigation into the unsaturated fatty acid content in sheep muscle uncovered mutations in genes like APOA17, CFHR5, TGFBR5, and LEPR associated with fatty acid composition [45]. Moreover, RNA-seq revealed differentially expressed mRNAs in the hypothalamus, pituitary, and ovary of Small-Tailed Han sheep and Tan sheep, exposing key genes implicated in estrogenic processes.…”
Section: Transcriptomicsmentioning
confidence: 99%
“…Further insights into the interaction between the candidate lncRNA MSTRG.259847.2 and its target gene SMAD2 were substantiated in sheep pituitary cells [44]. By utilizing RNA-seq, an investigation into the unsaturated fatty acid content in sheep muscle uncovered mutations in genes like APOA17, CFHR5, TGFBR5, and LEPR associated with fatty acid composition [45]. Moreover, RNA-seq revealed differentially expressed mRNAs in the hypothalamus, pituitary, and ovary of Small-Tailed Han sheep and Tan sheep, exposing key genes implicated in estrogenic processes.…”
Section: Transcriptomicsmentioning
confidence: 99%
“…Numerous research studies have been conducted in this area, contributing to a better understanding of the molecular mechanisms underlying lipid metabolism in these animals. Asep Gunawan et al [ 17 ] identified a possible candidate gene that controls the composition and metabolism of the sheep liver through transcriptomics analysis of unsaturated fatty acids (FA). Huang et al [ 18 ] compared the liver transcriptome of Jinhua pigs and landrace pigs and found that some differentially expressed genes were involved in the processes of redox, lipid synthesis, and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Improvingement of lamb quality is expected to increase the meat's nutritional value, of meat that iswhich benefitscial to human health. Therefore, To improve the genetics of sheep, breeding programs are recommended as one of the most realistic approaches performed using candidate genes through identification variant analysis to enhance the genetic of sheep [6,7]. A few studies by molecular genetics have been done and focussed on lamb, including lamb quality traits, carcass characteristics, fatty acid composition, A c c e p t e d A r t i c l e and flavor and odor.…”
Section: Introductionmentioning
confidence: 99%